1981
DOI: 10.1002/j.1551-8833.1981.tb04827.x
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of asbestos–cement pipe under various water quality conditions: Part 2, theoretical considerations

Abstract: A water chemical model involving the complexation and solubility equilibria of calcium, magnesium, zinc, iron, manganese, silica, chloride, orthophosphate, and carbonate has been developed and applied to laboratory pipe‐loop‐coupon and field data on asbestos–cement pipe. Calculation of the saturation states of the relevant solids enables graphic guides to be prepared for the prediction of dosage levels for in‐situ pipe coating by zinc compounds as well as protection afforded by coatings formed by natural inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…One key study evaluated the use of zinc and orthophosphate for the protection of cement-based piping materials (Schock & Buelow, 1981). One key study evaluated the use of zinc and orthophosphate for the protection of cement-based piping materials (Schock & Buelow, 1981).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One key study evaluated the use of zinc and orthophosphate for the protection of cement-based piping materials (Schock & Buelow, 1981). One key study evaluated the use of zinc and orthophosphate for the protection of cement-based piping materials (Schock & Buelow, 1981).…”
mentioning
confidence: 99%
“…Although much of the potable water distribution systems in the United States are composed of concrete or cement-lined pipe, little research has been conducted to evaluate the effect of phosphate, zinc, or zinc orthophosphate (ZOP) on cement degradation. One key study evaluated the use of zinc and orthophosphate for the protection of cement-based piping materials (Schock & Buelow, 1981). Those authors concluded that zinc provided significant protection for asbestos-cement pipe (as evidenced by lower leaching of calcium to the bulk water) and that the addition of orthophosphate alone protected metallic piping in the distribution system.…”
mentioning
confidence: 99%
“…However, if calcium carbonate is undersaturated, there is no reason to expect the saturation indices to predict with accuracy the dissolution of AC pipes, since calcium carbonate is only a minor constituent of cement. In this case, the aggressiveness of conveyed water to AC pipe will be dictated by other chemical equilibriums (Schock and Buelow, 1981). In addition, the indices fail to account for the protective coating of some of the elements in the water as discussed in following section.…”
Section: Ac Pipe Condition Assessmentmentioning
confidence: 99%
“…A theoretical explanation of the protection of AC pipe by zinc, iron, and calcium carbonate was given by Schock and Buelow (14). They concluded that the Aggressiveness Index (15) is not appropriate for predicting fiber release from AC pipe and deterioration of the inner wall of the pipe because the index fails to take into account possible protective constituents such as silica, iron, manganese, and zinc and because the pipe wall is primarily calcium silicate rather than calcium carbonate.…”
Section: Control Of Asbestos From Ac Pipesmentioning
confidence: 99%
“…They concluded that the Aggressiveness Index (15) is not appropriate for predicting fiber release from AC pipe and deterioration of the inner wall of the pipe because the index fails to take into account possible protective constituents such as silica, iron, manganese, and zinc and because the pipe wall is primarily calcium silicate rather than calcium carbonate. In regard to the use of zinc compounds for corrosion control, they concluded that the chloride, sulfate and orthophosphate salts of zinc protected AC pipe by formation of zinc hydroxycarbonate precipitate, but that only zinc orthophosphate also offered protection for metal pipe in systems containing both AC pipe and lead service lines or plumbing (14). In regard to the use of zinc compounds for corrosion control, they concluded that the chloride, sulfate and orthophosphate salts of zinc protected AC pipe by formation of zinc hydroxycarbonate precipitate, but that only zinc orthophosphate also offered protection for metal pipe in systems containing both AC pipe and lead service lines or plumbing (14).…”
Section: Control Of Asbestos From Ac Pipesmentioning
confidence: 99%